2006
DOI: 10.1074/jbc.m512964200
|View full text |Cite
|
Sign up to set email alerts
|

A Chondroitin Sulfate Chain Attached to the Bone Dentin Matrix Protein 1 NH2-Terminal Fragment

Abstract: Dentin matrix protein 1 (DMP1) is an acidic noncollagenous protein shown by gene ablations to be critical for the proper mineralization of bone and dentin. In the extracellular matrix of these tissues DMP1 is present as fragments representing the NH 2 -terminal (37 kDa) and COOH-terminal (57 kDa) portions of the cDNA-deduced amino acid sequence. During our separation of bone noncollagenous proteins, we observed a high molecular weight, DMP1-related component (designated DMP1-PG). We purified DMP1-PG with a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
101
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 66 publications
(104 citation statements)
references
References 32 publications
2
101
1
Order By: Relevance
“…This polyclonal antibody recognizes the COOH-terminal (57 kDa) fragment of DMP1 in both Western immunoblotting and immunohistochemical analyses; for the latter application, the immunoreaction of this polyclonal antibody is not as strong as that of the monoclonal antibody anti-DMP1-C-8G10.3 (see later). Both types of antibodies have been thoroughly characterized and previously used in Western immunoblotting for detection of the NH 2 -terminal or COOHterminal fragment of DMP1, respectively [13,19]. Western immunoblotting was performed as previously described [18].…”
Section: Sds-page and Western Immunoblottingmentioning
confidence: 99%
See 3 more Smart Citations
“…This polyclonal antibody recognizes the COOH-terminal (57 kDa) fragment of DMP1 in both Western immunoblotting and immunohistochemical analyses; for the latter application, the immunoreaction of this polyclonal antibody is not as strong as that of the monoclonal antibody anti-DMP1-C-8G10.3 (see later). Both types of antibodies have been thoroughly characterized and previously used in Western immunoblotting for detection of the NH 2 -terminal or COOHterminal fragment of DMP1, respectively [13,19]. Western immunoblotting was performed as previously described [18].…”
Section: Sds-page and Western Immunoblottingmentioning
confidence: 99%
“…For Western immunoblotting, two types of anti-DMP1 antibodies (Table 1) were used. One was a monoclonal antibody generated using the NH 2 -terminal fragment of rat bone DMP1 as the antigen [13]. This monoclonal antibody, designated anti-DMP1-N-9B6.3, reacts specifically with the NH 2 -terminal fragment of DMP1 in Western immunoblotting but shows a very weak reaction to DMP1 in immunohistochemical analysis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the ECM of both tissues does contain significant amounts of processed NH 2 -terminal and COOHterminal DMP1 fragments (Qin et al 2003). Recently, a proteoglycan form of the NH 2 -terminal fragment, designated as "DMP1-PG," was discovered in bone and dentin ECM (Qin et al 2006). Biochemical analysis showed that the COOH-terminal fragment of rat DMP1 contains 41 phosphates, whereas the NH 2 -terminal fragment has 12 phosphates.…”
mentioning
confidence: 99%